Infiltration of meningeal macrophages into the Virchow–Robin space after ischemic stroke in rats: Correlation with activated PDGFR-β-positive adventitial fibroblasts - Riew, Tae-Ryong; Hwang, Ji-Won; Jin, Xuyan; Kim, Hong Lim; Lee, Mun-Yong (Frontiers in Molecular Neuroscience, 2022)
Macrophages play a crucial role in wound healing and fibrosis progression after brain injury. However, a detailed analysis of their initial infiltration and interaction with fibroblasts is yet to be conducted. This study aimed to investigate the possible route for migration of meningeal macrophages into the ischemic brain and whether these macrophages closely interact with neighboring platelet-derived growth factor beta receptor (PDGFR-β)-positive adventitial fibroblasts during this process. A rat model of ischemic stroke induced by middle cerebral artery occlusion (MCAO) was developed. In sham-operated rats, CD206-positive meningeal macrophages were confined to the leptomeninges and the perivascular spaces, and they were not found in the cortical parenchyma. In MCAO rats, the number of CD206-positive meningeal macrophages increased both at the leptomeninges and along the vessels penetrating the cortex 1 day after reperfusion and increased progressively in the extravascular area of the cortical parenchyma by 3 days. Immunoelectron microscopy and correlative light and electron microscopy showed that in the ischemic brain, macrophages were frequently located in the Virchow–Robin space around the penetrating arterioles and ascending venules at the pial surface. This was identified by cells expressing PDGFR-β, a novel biomarker of leptomeningeal cells. Macrophages within penetrating vessels were localized in the perivascular space between smooth muscle cells and PDGFR-β-positive adventitial fibroblasts. In addition, these PDGFR-β-positive fibroblasts showed morphological and molecular characteristics similar to those of leptomeningeal cells: they had large euchromatic nuclei with prominent nucleoli and well-developed rough endoplasmic reticulum; expressed nestin, vimentin, and type I collagen; and were frequently surrounded by collagen fibrils, indicating active collagen synthesis. In conclusion, the perivascular Virchow–Robin space surrounding the penetrating vessels could be an entry route of meningeal macrophages from the subarachnoid space into the ischemic cortical parenchyma, implying that activated PDGFR-β-positive adventitial fibroblasts could be involved in this process.